Pesaguan Dayak Kanjan Serayong Custom: The Relationship between Catholic Faith and Culture - Endi, Yohanes; Ranubaya, Fransesco Agnes; Watu, Christianus (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
Integrating Catholicism and Kanjan Serayong culture within the Pesaguan Dayak community exemplifies the dynamic interplay between religious and cultural rituals, particularly in funeral ceremonies, fostering communal solidarity and cultural resilience through a seamless blend of traditional and Catholic practices. This research aims to elucidate how these cultural and religious elements coexist and reinforce each other within the community. Employing qualitative methods, the study includes interviews with three Pesaguan Dayak Indigenous Leaders and informants, participant observations, and literature analysis guided by Victor Turner's theory of ritual structure. The findings highlight that both Catholicism and Kanjan Serayong culture places a strong emphasis on rituals, particularly funeral ceremonies, which are central to honoring the deceased and fostering communal solidarity. The study reveals a profound respect for sacred traditions and cultural heritage, showing that rituals reflect a seamless blend of Catholic and indigenous practices, indicative of cultural adaptation and resilience. This research underscores the need for further studies on cultural inculturation within Indigenous communities, comparative analyses across different cultural contexts, and interdisciplinary collaborations to enhance the understanding of Indigenous spirituality and cultural heritage preservation. Additionally, this study recommends involving local communities in the research process to promote mutual learning and effective cultural preservation strategies.